Penanganan Gelandangan dan Pengemis di Dinas Sosial Kabupaten Karawang - Indriyani, Indriyani; Sungkono, Sungkono; Karnama, Maman Mulya (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
Work practice isacompulsorysubjectintheformofstudentpractical work  placementactivities,toprovideinsightinto theapplicationofknowledgeinthebusiness/workworld.Studentspracticetheirabilitiesandknowledgeinanalyzing problems related to the field of study program that occur in the world of work. The social service, in the fieldofsocialrehabilitation,providesservicesintheformofhandlinghomelesspeopleandbeggars,displacedpeople, children and the elderly as well as providing assistance to people in Karawang who cannot afford. The method used in this research is descriptive and librry research.   Based on the results of practical work regarding the handling of homeless people and beggars at the Karawang Regency Social Service, it can be concluded that the handling of homeless people and beggars in Karawang Regency has not been carried out properly due to lack of human resources and budget to carry out these activitiesWork practice isacompulsorysubjectintheformofstudentpractical work  placementactivities,toprovideinsightinto theapplicationofknowledgeinthebusiness/workworld.Studentspracticetheirabilitiesandknowledgeinanalyzing problems related to the field of study program that occur in the world of work. The social service, in the fieldofsocialrehabilitation,providesservicesintheformofhandlinghomelesspeopleandbeggars,displacedpeople, children and the elderly as well as providing assistance to people in Karawang who cannot afford. The method used in this research is descriptive and librry research.   Based on the results of practical work regarding the handling of homeless people and beggars at the Karawang Regency Social Service, it can be concluded that the handling of homeless people and beggars in Karawang Regency has not been carried out properly due to lack of human resources and budget to carry out these activities.